Pengaruh Variasi Pencampuran Tepung Terigu Dan Tepung Ikan Roa (Hermihampus Sp) Terhadap Sifat Fisik, Organoleptik Dan Kadar Protein pada Stik Ikan Roa - Asih, Esthy Rahman; Siswati, Tri; Il Ummi.B, Zu’aimana Lu’lu (Poltekkes Kemenkes Yogyakarta, 2023)
This study aims to find out the influence of variations in mixing wheat flour and roa fish meal on physical, organoleptic, and protein levels of sticks for stunting prevention foods. This study was laboratorium experimental study. There were 4 trial (k = 4) using twice repetition (i = 2). Each repetition consist of 2 unit trial (n = 2), then the total were16 unit trial. We performed four ratio wheat flour and roa fish including 100%:0%, 90%:10%, 80%:20%, 70%:30%. The processing food was conducted in food technology laboratorium nutrition department Poltekkes Kemenkes Yogyakarta, while the protein level tested in Laboratorium Pusat Studi Pangan dan Gizi, UGM Yogyakarta. Setting on May 2022 involving 25 semi-experts panelists for hedonic tets We performed kruskal walis for identified the panelist favourite. Result showed that the more roa fish meal mixture the more brown the color, the more distinctive the aroma of roa fish, the crisp texture and savory taste. Panelists prefer snacks with a composition of 90%: 10%.